2014
DOI: 10.1128/iai.01292-13
|View full text |Cite
|
Sign up to set email alerts
|

The Type II Secretion Pathway in Vibrio cholerae Is Characterized by Growth Phase-Dependent Expression of Exoprotein Genes and Is Positively Regulated by σ E

Abstract: c Vibrio cholerae, an etiological agent of cholera, circulates between aquatic reservoirs and the human gastrointestinal tract. The type II secretion (T2S) system plays a pivotal role in both stages of the lifestyle by exporting multiple proteins, including cholera toxin. Here, we studied the kinetics of expression of genes encoding the T2S system and its cargo proteins. We have found that under laboratory growth conditions, the T2S complex was continuously expressed throughout V. cholerae growth, whereas ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 51 publications
(79 reference statements)
0
25
1
Order By: Relevance
“…Concurrent with our experiments, another study found that two promoters were predicted to be upstream of epsC; the downstream promoter was predicted to be 70 dependent, while the upstream promoter was E dependent (26). Moreover, two V. cholerae DGCs were shown to induce an epsC-lux transcriptional fusion in E. coli (26).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Concurrent with our experiments, another study found that two promoters were predicted to be upstream of epsC; the downstream promoter was predicted to be 70 dependent, while the upstream promoter was E dependent (26). Moreover, two V. cholerae DGCs were shown to induce an epsC-lux transcriptional fusion in E. coli (26).…”
mentioning
confidence: 70%
“…2). These transcriptional (26). In that study, the E 5= promoter was named P2, while the 70 3= promoter was named P1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assays were conducted in 50 mM Tris-HCl, 150 mM NaCl, 5 mM CaCl 2 , pH 7.6, and 25 g/ml DQ gelatin for 10 min at 37°C using excitation and emission wavelengths of 485 Ϯ 10 and 530 Ϯ 15 nm, respectively. The detected change in fluorescence was normalized by either the optical density of the cultures (OD 600 ) or VchC concentration (28). The effect of different inhibitors, including 1,10-phenanothroline (5 mM), EDTA (5 mM), EGTA (5 mM), leupeptin (1 mM), phenylmethylsulfonyl fluoride (PMSF; 5 mM), N-methylmaleimide (5 mM), and benzamidine (5 mM), on VchC proteolytic activity also was studied.…”
Section: Methodsmentioning
confidence: 99%
“…However, a particularly interesting and recent finding is that one of the promoters driving expression of the epsC-N operon is RpoE-dependent. 79 One possible rationale for this control is to ensure increased T2SS production and virulence factor export when V. cholerae enters its host, where it encounters RpoE-inducing stimuli such as CAMPs and altered environmental conditions. An alternative rationale, suggested by removal of the T2SS compromising envelope integrity, is that increased production of the T2SS is an important component of the RpoEdependent envelope stress-reduction mechanism.…”
mentioning
confidence: 99%